Anomalous origin of the coronary artery: prevalence and coronary artery disease in adults undergoing coronary tomographic angiography - Li, Kunyan; Hu, Ping; Luo, Xiaolin; Li, Furong; Chen, Ling; Zhao, Junyong; Wang, Zelan; Luo, Wenjian; Jin, Jun; Qin, Zhexue (BMC cardiovascular disorders, 2024)
Anomalous aortic origin of a coronary artery (AAOCA) is a rare congenital coronary anomaly with the potential to cause adverse cardiac events. However, there is limited data on the association between AAOCA and coronary artery disease (CAD). Therefore, the aim of this study is to determine the prevalence and symptoms of patients with AAOCA, as well as investigate the correlation between AAOCA and CAD in a population referred for coronary computed tomographic angiography (CTA). All consecutive patients who underwent CTA from 2010 to 2021 were included. Characteristics, symptoms, coronary related adverse events and CTA information were reviewed by medical records. Separate multivariable cumulative logistic regressions were performed, using the stenosis severity in each of the four coronaries as individual responses and as a combined patient clustered response. Finally, we identified 207 adult patients with AAOCA, the prevalence of AAOCA is 0.23% (207/90,501). Moreover, this study found no significant association between AAOCA and CAD. AAOCA did not contribute to higher rates of hospitalization or adverse cardiac events, including calcification. AAOCA is a rare congenital disease that is not associated with increased presence of obstructive CAD in adults.